CLIMATE DISINFORMATION AND DIGITAL MOBILIZATION: HEATWAVES IN BRAZIL AND SOCIO-ENVIRONMENTAL JUSTICE - Monteiro Júnior, Francisco Hélio; Linhares, Thales Cavalcante (Seven Editora, 2025)
The year 2024 was the hottest ever recorded in Brazil, with an average temperature of 25.02°C, revealing the intensification of the climate crisis. Paradoxically, climate risk denial almost doubled, rising from 5% to 9% of the population, according to Datafolha. This contradiction reveals an epistemic and communicational crisis that undermines public understanding of global warming. This study aims to analyze how climate disinformation circulates in Brazil, compromising adaptation and mitigation policies. To this end, a qualitative and documentary approach was adopted, grounded in Luciano Floridi’s concept of the infosphere and supported by INMET data, UN reports, and recent scientific literature. Findings indicate that the contamination of the infosphere by false narratives—amplified by social media and political groups—functions as an active environmental risk vector, turning disinformation into an instrument of symbolic and economic power. The results demonstrate that confronting the climate crisis also requires protecting the informational environment. It is concluded that future sustainability depends on an epistemic governance capable of integrating science, technology, and cognitive justice, ensuring that climate information remains a public good guided by truth and the preservation of life.DOI: https://doi.org/10.56238/sevened2025.036-064